Indian Jews: an annotated bibliography : 1665 - 2005 - Katz, Nathan (Manohar, 2013)
This bibliography is designed to assist students and scholars who wish to explore India's rich and varied Jewish heritage. It is also intended for the more casual reader, especially Indian Jews themselves whether at home in India or relocated in Israel, the United States, England or Australia. It begins with Menasseh ben Israel's 1665 book, and 2005 was selected as a point of closure